ALKAWAKIB IS A PILOT SCHOOL BASED ON CHARACTER AND CHARACTER-BASED SCHOOL IN INDONESIA - Meidianas Saputra; Nana Sepriyanti; Martin Kustati (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the implementation of the Alkawakib Model of a Model School Based on Adab and Character in Indonesia as a character education innovation oriented towards the formation of adab as the main foundation of learning. The research is motivated by the increasing number of character issues of students that indicate a gap between national education goals and educational practices in schools. The study uses a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, documentation studies, and analysis of various habituation programs implemented at Alkawakib School. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña through the process of data condensation, data presentation, and drawing conclusions. The results show that the successful implementation of adab-based schools is supported by the integration of adab values ​​in the curriculum, exemplary leadership and teachers, systematic daily habits, strategic partnerships with parents, a continuous monitoring system, and a consistent school culture. This model is able to shape the religious character, discipline, responsibility, social awareness, and independence of students in a sustainable manner. This study concludes that the Alkawakib model is worthy of being used as a model for developing schools based on manners and character that can be replicated in various educational units in Indonesia.